Carrier‐Type Modulation and Mobility Improvement of Thin MoTe2. Issue 39 (28th August 2017) - Qu, Deshun; Liu, Xiaochi; Huang, Ming; Lee, Changmin; Ahmed, Faisal; Kim, Hyoungsub; Ruoff, Rodney S.; Hone, James; Yoo, Won Jong
Abstract: A systematic modulation of the carrier type in molybdenum ditelluride (MoTe2 ) field‐effect transistors (FETs) is described, through rapid thermal annealing (RTA) under a controlled O2 environment (p‐type modulation) and benzyl viologen (BV) doping (n‐type modulation). Al2 O3 capping is then introduced to improve the carrier mobilities and device stability. MoTe2 is found to be ultrasensitive to O2 at elevated temperatures (250 °C). Charge carriers of MoTe2 flakes annealed via RTA at various vacuum levels are tuned between predominantly pristine n‐type ambipolar, symmetric ambipolar, unipolar p‐type, and degenerate‐like p‐type. Changes in the MoTe2 ‐transistor performance are confirmed to originate from the physical and chemical absorption and dissociation of O2, especially at tellurium vacancy sites. The electron branch is modulated by varying the BV dopant concentrations and annealing conditions. Unipolar n‐type MoTe2 FETs with a high on–off ratio exceeding 10 6 are achieved under optimized doping conditions. By introducing Al2 O3 capping, carrier field effect mobilities (41 for holes and 80 cm 2 V −1 s −1 for electrons) and device stability are improved due to the reduced trap densities and isolation from ambient air. Lateral MoTe2 p–n diodes with an ideality factor of 1.2 are fabricated using the p‐ and n‐type doping technique to test the superb potential of the doping method in functional electronic device applications. Abstract : Unipolar p‐ and n‐type molybdenum ditelluride (MoTe2 ) field‐effect transistors are achieved through controllable doping techniques. With Al2 O3 capping, hole and electron mobility are improved to 41 and 80 cm 2 V −1 s −1, respectively. Lateral MoTe2 p–n diodes with an ideality factor of 1.2 are fabricated by combining the p‐ and n‐type doping techniques.